Effects of Salvia Officinalis Extract on the Breast Cancer Cell Line - Habibeh Zare (Ital Publication, 2019)
Background: Common sage (Salvia officinalis L., Lamiaceae) is an aromatic and medicinal plant well known for its antioxidant properties. This plant belongs to Lamiaceae family and has many pharmaceutical properties. Some in vivo studies have shown the biological antioxidant effects of sage. As a member of Salvia officinalis Labiatae, sage is also known as "Maryam flower" in Iran. Sage importance lies in its therapeutic potential. It has been exploited as an anti-spasmodic, astringent, sedative, anti-hyperglycemic, and anti-inflammatory agent in Iranian medicine. Objective: Studying the anticancer effects of the compounds in Salvia officinalis extracts, such as cineol and camphor. Methods: Cancer was induced by DMBA (dimethyl-benzantheracene) dissolved in sunflower oil for 4 weeks. The case group was treated with sage leaf hydroalcoholic extract for 4 weeks; while the controls received distilled water. Result: Angiogenesis is a key process in cancer spread and metastasis. The hydroalcoholic extract of garden sage halted angiogenesis in the breast cell line of both human and mouse models; the highest impact was observed in hexane extract. Findings indicated the therapeutic effects of garden sage (i.e. its in vitro anti-angiogenesis activity and anti-migratory properties). Conclusion: Saliva officinalis can potentially prevent breast cancer.